Pemberdayaan Masyarakat Mengenai Kepatuhan Diet dan Pengobatan Hipertensi - Nita Arisanti Yulanda; M. Ali Maulana; Ikbal Fradianto; Djoko Priyono (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Hypertension is a non-communicable disease with an increasing incidence, especially in the elderly. One of the reasons is that many sufferers do not routinely even take medication after experiencing hypertension. In addition to medication, dietary factors can also increase the risk of an increase in blood pressure. Community service is expected to be able to help health problems independently. Community empowerment is carried out by introducing regional conditions, introspective surveys, deliberation, participatory planning, implementation of activities, and sustainability development. The implementation is carried out by providing health education about hypertension diet and medication adherence by using poster media entitled “CAT HITAM” during a pandemic, before and after the activity, pretest-posttest is carried out to determine dietary knowledge and medication adherence for hypertension sufferers, Health Education regarding activities that can be done, recommended food consumption, and medication adherence that hypertension sufferers must adhere to during a pandemic. The pretest-posttest results showed differences in knowledge of diet and medication before and after health education with a p-value <0.05. Dietary problems from the results of community assessments are mostly about the limits of salt consumption for hypertension and treatment. Most of the respondents said they stopped treatment because they felt they had no complaints. It needs cooperation from various parties to continuously motivate the elderly to follow the rules of diet and treatment of hypertension.